MANAJEMEN PEMERINTAH KOTA TERHADAP RUANG TERBUKA HIJAU DI KOTA PEKANBARU TAHUN 2008-2012 - Ajeng Puspita Ningrum; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was motivated by the lack of green open space (RTH) in the city of Pekanbaru and not achieving the target of 30% non-compliance of green open space in accordance with the Law No. 26 Year 2007 on Spatial Planning.The purpose of this penelitaan to know how government management of Pekanbaru to the green open space in the city of Pekanbaru Year 2008-2012 and what factors influence that affects the city government in promoting green open space (RTH) in Pekanbaru.Type of research method used was qualitative research can be said to be adequate to be applied. Understanding qualitative research can be defined as research that produces descriptive data about the words spoken or written, and the observable behavior of the people studied.In explaining the research problems using the theory of Local Government Management G.R.Terry used to guide the research analysis. This study used informant informant as information objects that aim to achieve mastery in getting the information in this study. Types and sources of data used in this study is primary data and secondary data obtained through observation.Based on the findings in this study that the Law No. 26 Year 2007 on Spatial Planning and Government Regulation No. 26 Year 2008 on National Spatial Plan requires City area has 30% green open space of the area of the city is, but in reality the City Pekanbaru Keith can meet the needs of green open space (RTH) is. This is because the factors that influence the management of the city government to green open space (RTH) is the following local government planning, organizing regional government institutions, the use of the resources of local government (personnel resources, natural resources, artificial resources, social resources, finance, and equipment), the supervision of the regional administration.Keywords: Management, government, Green Open Space.